(untitled) - Ahmad, Asmala; Hashim, Mazlan; Ayof, Mohd Nizam; Budi, Agus Setyo; Sakidin, Hamzah; S. Ahmad, S. Sakinah (University Utara Malaysia, 2005)
Particulate matter sizing less than 10 micrometers or widely known PM10, is one of the major constituents of thick haze phenomenon, which occured in Malaysia during September 1997. In this study, seven scenes of NOAA-14 AVHRR satellite data were acquired in order to determine and map PM10 over Malaysia. Five locations of air pollution station were chosen where PM10 was measured. Band 1 (wavelengths of 0.58-0.68 micrometers) of NOAA-14 AVHRR satellite data were converted from digital numbers to reflectance prior to deriving PM10 information from the imagery. Cloud separation was then carried out by integrating both visual and thresholding technique. Relationship between the satellite reflectance and the corresponding PM10 AQI (Air Quality Index)at the stations were established using linear regression model. The model was then used to map the concentration of PM10 over Malaysia. The result indicates that remote sensing technique using band 1 of NOAA-14 AVHRR data was capable to determine and map PM10 concentration quantitatively. Finally, accuracy was assessed using RMSE technique.